Answer:
f(-3)=5x^2+5x*3
-f*3=5x^2+5*3x
-3f=5x^2+15x
f=-5x(x+3)/3
f(-9)=5x^2+5x*3
-f*9=5x^2+5*3x
-9f=5x^2+15x
f=-5x(x+3)/9
Step-by-step explanation:
hope it helps you?
Answer:
Multiply both sides by five
Move -65 to the right
calculate 100+65
x=165
Answer:
Her uncle's age = 47 years
Step-by-step explanation:
Sophia = 12 years old
Her Uncle Reynald tells her that if she adds 5 to her age,
= 12 + 5
multiplies the sum by 3
= (12 + 5) × 3
and then subtracts 4 from the product
= {(12 + 5) × 3} - 4
she will find his age
{(12 + 5) × 3} - 4
= (17 × 3) - 4
= 51 - 4
= 47
Her uncle's age = 47 years
Sophia wrote:
12 + 5 × 3 − 4
Using PEMDAS
P - product
E - exponent
M - multiplication
D - division
A - addition
S - subtraction
Sophia's expression can be written as = 12+(5*3)-4
= (12 + 15) - 4
= 27 - 4
= 23
Sophia's expression is wrong
Answer:
a. x = 13m, b. x = 12cm
Step-by-step explanation:
a. x² = 12² + 5² (Pyth. theorem)
x = 13 m
b. 15² = 9² + x² (Pyth. theorem)
x = 12 cm
Answer:
600 in^2.
Step-by-step explanation:
There are 6 faces on a cube so the area we need is:
6 * 10 * 10
= 600 in^2.